Robot Mobile Penjejak Arah Cahaya Dengan Kendali Logika Fuzzy - Wisnu Aribowo, Fajar; Fatchur Rochim, Adian; Setiawan, Iwan (Transmisi, 2008)
Two DC Motor Velocity Control for differential drive can applicate Mobile Robot Driver. Each Velocity control make Smoothness Mobile robot for straight move to search object target. Resolving this problem need Controller for control each of Motor Velocity. Fuzzy logic used this controller. Fuzzy logic is one of flexyble Control system method to get difficulty systems no need Mathematic Models.  For this research, Fuzzy control nedd for Motor velocity driver to get light source, Microcontroller 8bit M68HC11 Motorola based.keyword : Fuzzy Logic, Driver, Motor Vehicle